ETR2 is an ETR1-like gene involved in ethylene signaling in Arabidopsis - Sakai, Hajime (The National Academy of Sciences, 1998)
The plant hormone ethylene regulates a variety of processes of growth and development. To identify components in the ethylene signal transduction pathway, we screened for ethylene-insensitive mutants in Arabidopsis thaliana and isolated a dominant etr2-1 mutant. The etr2-1 mutation confers ethylene insensitivity in several processes, including etiolated seedling elongation, leaf expansion, and leaf senescence. Double mutant analysis indicates that ETR2 acts upstream of CTR1, which codes for a Raf-related protein kinase. We cloned the ETR2 gene on the basis of its map position, and we found that it exhibits sequence homology to the ethylene receptor gene ETR1 and the ETR1-like ERS gene. ETR2 may thus encode a third ethylene receptor in Arabidopsis, transducing the hormonal signal through its “two-component” structure. Expression studies show that ETR2 is ubiquitously expressed and has a higher expression in some tissues, including inflorescence and floral meristems, petals, and ovules.